POTENTIAL OF DRUG INTERACTIONS IN HOSPITALIZED PATIENTS RECEIVING WARFARIN THERAPY FOR THE FIRST TIME - OKTIANTI, DIAN; CHOLISOH, ZAKKY; GHADZI, SITI MAISHARAH SHEIKH; KARUNIAWATI, HIDAYAH (International Journal of Applied Pharmaceutics, 2025)
Objective: To identify potential interactions between warfarin and other drugs in hospitalized patients receiving warfarin therapy for the first time and determine parameters that are predicted to increase the risk of drug interactions resulting in major clinical severity. This is the first study in the field that was conducted in a multicenter setting in Central Java. Methods: Data on the use of concomitant drugs with warfarin were collected from the medical records of hospitalized patients (August 2023-July 2024) who first received warfarin in a retrospective, multicentre study at 4 hospitals. Potential drug interaction was analyzed using a drug interaction checker. Results: There were 148 patients who met the criteria, 78 patients (53%) were male and aged between 40-64 y. 78 patients (52%) received more than 8 types of drugs. Potential drug interactions occurred in all patients (100%), 62 patients (46.62%) experienced interactions in 6-8 drugs used. The parameter that had the strongest association with the severity of potential drug interactions was the number of drugs consumed with an Adjusted Odds Ratio (AOR) of 3.097 (95% CI 1.495-6.417) and a p-value of 0.002 (p<0.05) and Length of Stay (LOS) with an AOR of 0.344 (95% CI 0.125-0.945 and a p-value 0.038 (p<0.05). Conclusion: All hospitalized patients receiving first-time warfarin therapy experienced potential drug interaction events. The strongest predictors contributing to potential drug interactions with major clinical impact severity were the number of drugs taken at the normal dose and length of stay.